Foundation design Course and corrected application exercises - BENSOULA, Mohamed (My University, 2024)
The foundation is the part of a building or civil engineering structure that transmits loads (own weight, climatic forces, seismic forces and operating loads) to the ground. Foundations are very important elements in construction, as they form the structural part that ensures its load-bearing capacity and controls settlement due to the loads it applies to the ground and infiltration due to the possible presence of water in the soil. Depending on the bearing capacity of the soil, the environment in which the structure is to be built and the admissible settlements, the builder can choose the type of foundation: shallow, semi-submerged or deep. This handout is intended for students of master's degree in civil engineering. The course material and corrected exercises are divided into 3 chapters. The first chapter is devoted to shallow foundations, with a detailed discussion of insulated footings, threaded footings and inverts. The second chapter is devoted to deep foundations and finally a third chapter covers 10 application exercises with solutions relating to the first two chapters. Keywords : Foundation, Soil, Footing, Deep, Superficial, Stress.
Keywords: Foundation; Soil; Footing; Deep; Superficial; Stress